Evaluating Cryoablation of Metastatic Lung Tumors in Patients—Safety and Efficacy: The ECLIPSE Trial—Interim Analysis at 1 Year. Issue 10 (October 2015) - de Baere, Thierry; Tselikas, Lambros; Woodrum, David; Abtin, Fereidoun; Littrup, Peter; Deschamps, Frederic; Suh, Robert; Aoun, Hussein D.; Callstrom, Matthew
Abstract : Introduction: To assess the feasibility, safety and local tumor control of cryoablation for treatment of pulmonary metastases. Materials and Methods: This Health Insurance Portability and Accountability Act (HIPAA) compliant, IRB-approved, multicenter, prospective, single arm study included 40 patients with 60 lung metastases treated during 48 cryoablation sessions, with currently a minimum of 12 months of follow-up. Patients were enrolled according to the following key inclusion criteria: 1 to 5 metastases from extrapulmonary cancers, with a maximal diameter of 3.5 cm. Local tumor control, disease-specific and overall survival rates were estimated using the Kaplan–Meier method. Complications and changes in physical function and quality of life were also evaluated using Karnofsky performance scale, Eastern Cooperative Oncology Group performance status classification, and Short Form-12 health survey. Results: Patients were 62.6 ± 13.3 years old (26–83). The most common primary cancers were colon (40%), kidney (23%), and sarcomas (8%). Mean size of metastases was 1.4 ± 0.7 cm (0.3–3.4), and metastases were bilateral in 20% of patients. Cryoablation was performed under general anesthesia (67%) or conscious sedation (33%). Local tumor control rates were 56 of 58 (96.6%) and 49 of 52 (94.2%) at 6 and 12 months, respectively. Patient's quality of life was unchanged over the follow-up period. One-year overall survival rate was 97.5%. The rate of pneumothorax requiring chest tube insertion was 18.8%. There were three Common Terminology Criteria for Adverse Events grade 3 procedural complications during the immediate follow-up period (pneumothorax requiring pleurodesis, noncardiac chest pain, and thrombosis of an arteriovenous fistula), with no grade 4 or 5 complications. Conclusion: Cryoablation is a safe and effective treatment for pulmonary metastases with preserved quality of life following intervention.